UV Photocatalytic Activity for Water Decomposition of SrxBa1−xNb2O6 Nanocrystals with Different Components and Morphologies - Guoqiang Han; Shuguang Cao; Bo Lin (Journal of Chemistry)
Strontium barium niobate SrxBa1-xNb2O6 (SBN) nanocrystals with different components (x=0.2, 0.4, 0.6, and 0.8) were synthesized by Molten Salt Synthesis (MSS) method at various reaction temperatures (T = 950°C, 1000°C, 1050°C, and 1100°C). The SBN nanocrystals yielded through flux reactions possess different morphologies and sizes with a length of about ~100 nm~7 μm and a diameter of about ~200~500 nm. The Scanning Electron Microscopy (SEM) and X-ray Diffraction (XRD) techniques were used to study the compositions, structures, and morphologies of the nanocrystals. The absorption edges of the SBN nanocrystals are at a wavelength region of approximate 390 nm, which corresponds to band-gap energy of ~3.18 eV. The SBN nanocrystals with different sizes display different photocatalytic activity under ultraviolet light in decomposition of water. The SBN60 nanocrystals exhibit stable photocatalytic rates (~100~130 μmol of H2·g−1·h−1) for hydrogen production. The SBN nanocrystals can be a potential material in the application of photocatalysis and micro/nanooptical devices.